2023
DOI: 10.3390/s23115237
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Survey of Data Augmentation of ECG Signals for AI Applications

Abstract: AI techniques have recently been put under the spotlight for analyzing electrocardiograms (ECGs). However, the performance of AI-based models relies on the accumulation of large-scale labeled datasets, which is challenging. To increase the performance of AI-based models, data augmentation (DA) strategies have been developed recently. The study presented a comprehensive systematic literature review of DA for ECG signals. We conducted a systematic search and categorized the selected documents by AI application, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 144 publications
1
5
0
Order By: Relevance
“…However, based on our trials, the trio of signal transformations discussed previously proved optimal for our distinct task and dataset. This aligns with Rahman et al's systematic review [37]…”
Section: Augmentationsupporting
confidence: 89%
“…However, based on our trials, the trio of signal transformations discussed previously proved optimal for our distinct task and dataset. This aligns with Rahman et al's systematic review [37]…”
Section: Augmentationsupporting
confidence: 89%
“…In this proof-of-concept study, we demonstrated that performant ML algorithms can be trained on Ca 2+ fluctuations in activated monoclonal T cells to predict polyclonal T cell responses, using a limited amount of data (~10,000 cells). Substantially increasing the size of the dataset with additional time lapses or through AI-assisted methods may further improve model performance, especially when it comes to differentiating the distinct pattern of Ca 2+ fluctuation associated with nonspecific T cells mispredicted as antigen-specific from bona fide antigen-specific T cells ( 43 – 45 ). Furthermore, it has been previously demonstrated that Ca 2+ oscillations contain information about the affinity of TCR-pMHC interactions; lower affinity TCR engagement will typically lead to more transient Ca 2+ fluctuations and distinct early activation dynamics ( 14 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Basic data augmentation techniques encompass flipping, snipping, and introducing noise. In addition to these techniques, some other basic data augmentation techniques such as spatial inversion [11], time-spatial inversion [6], baseline wandering [20] are also applied to ECG signals. However, when it comes to the management of complex data such as medical imaging, these basic techniques are inadequate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, when it comes to the management of complex data such as medical imaging, these basic techniques are inadequate. The variational autoencoder (VAE) [20] is a deep model that has received less attention compared to other more widely adopted techniques. Nevertheless, a prominent concern revolves around the recurrent occurrence of hazy and indistinct output images.…”
Section: Literature Reviewmentioning
confidence: 99%